2012
DOI: 10.1371/journal.pmed.1001290
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Three Antiretroviral Regimens for Initial Treatment of HIV-1: A Randomized Clinical Trial in Diverse Multinational Settings

Abstract: Thomas Campbell and colleagues report findings of a randomized trial conducted in multiple countries regarding the efficacy of antiretroviral regimens with simplified dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(155 citation statements)
references
References 31 publications
7
142
1
2
Order By: Relevance
“…Similarly, participants who achieved a two-log decline in HIV RNA after four weeks of ART demonstrated a shorter time to virologic suppression (12 [8][9][10][11][12][13][14][15][16] vs. 24 [12][13][14][15][16][17][18][19][20][21][22][23][24] weeks, p<0.001; Figure 3B). blips, compared to four of 29 (13.8%) in the group that did not achieve this viral load target (p=1.00).…”
Section: Time To Virologic Suppressionmentioning
confidence: 98%
“…Similarly, participants who achieved a two-log decline in HIV RNA after four weeks of ART demonstrated a shorter time to virologic suppression (12 [8][9][10][11][12][13][14][15][16] vs. 24 [12][13][14][15][16][17][18][19][20][21][22][23][24] weeks, p<0.001; Figure 3B). blips, compared to four of 29 (13.8%) in the group that did not achieve this viral load target (p=1.00).…”
Section: Time To Virologic Suppressionmentioning
confidence: 98%
“…Commonly cited examples are lack of infrastructure, heterogeneity of resource availability among countries, unfamiliarity with clinical trial regulations, cultural/ethical issues, and other legal constraints around data-sharing. The few examples of large-scale clinical trials conducted in LMICs for HIV/AIDS and cervical cancer screening serve as valuable models for clinical trial design for gynecologic malignancies (Sankaranarayanan et al, 2009, Campbell et al, 2012, Adefuye et al, 2013). Unfortunately, oncologic treatment requires the expertise of multidisciplinary physicians and ancillary staff as well as the accompanying operating room equipment, chemotherapeutics, imaging machines and/or radiation therapy (RT) machines that can add an additional, and potentially prohibitive, layer of expense.…”
Section: Introductionmentioning
confidence: 99%
“…A remarkable strength of this study is the long follow-up period in comparison with clinical trials and other prospective cohort studies published to date [6,7,10,24]. Of interest, the median time to CRDRF event was 3.6 years, which is much longer than most follow-up periods in other studies.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, large clinical trials with long follow-up periods of more than 144 weeks in naïve patients have shown a renal safety profile of ART containing TDF, either similar to other ART without it, or with small significant declines in the estimated glomerular filtration rate (eGFR) of clinical implications difficult to ascertain [7][8][9]. Observational studies with longer follow-up periods suggest a more deleterious effect on the renal function, and point that TDF is associated with a higher incidence of chronic kidney disease [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%